Polyphonic narrative technique in Louise Erdrich’s “The plague of doves” - Mirzayeva, Parvina (The Lingua Spectrum, 2025)
This article analyzes the polyphonic (multi-voiced) narrative technique employed in the novel “The Plague of Doves” by contemporary American writer Louise Erdrich. The novel features multiple narrators – Evelina Harp, Mooshum, Judge Antone Bazil Coutts, and Cordelia Lochren – each creating an independent narrative layer through their distinct voices, language, and worldview. Through this multi-voiced structure, the author artistically conveys the complexity of human consciousness, the multilayered nature of memory, and the relativity of truth. The study is based on Mikhail Bakhtin’s theory of polyphony, examining the interaction of voices in the novel’s composition as well as their differences in language, rhythm, and logic. By employing this technique, Erdrich decentralizes the authorial voice, transforming the reader into an active listener and creating a textual space of multiple truths and dialogic interaction. As a result, “The Plague of Doves” emerges not only as a formally innovative work but also as a literary text that introduces a new dialogic mode of artistic thought.